Analysis of Kediri Cooperatives’ Perceptions of the 2023 Self-Declaration Circular Implementation - Yani Ahmad; Achmad Munif; M. Soleh Mauludin (Journal of Public Power, 2026)
The self-declaration policy in the P2SK Law and in Circular Letter No. 7 of 2023 from the Deputy for Cooperatives serves as a key instrument for classifying cooperative business models as closed-loop (member services) or open-loop (public services). This study aims to analyse the policy literacy of cooperative managers in Kediri City regarding the implementation of the Self-Declaration policy, particularly concerning their understanding of business classification, regulatory implications, and institutional readiness during the transition of supervision to the Financial Services Authority (OJK). The novelty of this study lies in its focus on policy literacy and the perceptions of cooperative managers as key factors in determining institutional responses to cooperative business classification policies. This area has so far been rarely examined in research on cooperatives in Indonesia. The study employs a qualitative approach using a phenomen logical design. Data was obtained through in-depth interviews with cooperative managers and officials from the Kediri City Cooperative Office, as well as a documentary review of self-declaration forms and cooperative administrative documents. The research findings indicate that all cooperatives included in the study opted for closed-loop status. This decision was influenced by limited policy literacy, perceptions regarding the complexity of OJK supervision, and a desire to maintain the identity of member-based cooperatives. This study concludes that the implementation of the Self-Declaration policy requires the strengthening of policy literacy, regulatory guidance, and the enhancement of cooperatives’ digital administrative capacity so that the supervisory transition process can proceed more effectively.